Contribution of within-litter interactions to individual differences in early postnatal growth in the domestic rabbit. (October 2015) - Bautista, Amando; Zepeda, José Alfredo; Reyes-Meza, Veronica; Martínez-Gómez, Margarita; Rödel, Heiko G.; Hudson, Robyn
Abstract : Interactions with littermates are an important component of the early environment of altricial mammals, frequently with major consequence for individual development, growth and survival. Early differences in starting mass within litters are often predictive of individual differences in behaviour and development, although to what extent such differences are independent of (epi)genetic factors is not always clear. In our study on domestic rabbits, Oryctolagus cuniculus, we created experimentally mixed litters consisting of either heavier or lighter pups obtained from different litters at birth and raised by foster mothers. We hypothesized that pups' body mass relative to their new littermates would determine the nature of their social interactions with consequences for their early growth, largely independent of their absolute or relative body mass in their litters of origin. As predicted, pups with a higher starting mass on postnatal day 1 compared to members of their new litter consistently had more neighbours in the litter huddle, thus reflecting their more central position. In turn, pups with more neighbours had relatively higher body temperatures, greater milk intake and a higher milk conversion ratio, resulting in relatively greater growth during the first critical postnatal week. Relative body mass in the litter of origin or absolute body mass had no notable effect, indicating that the observed developmental patterns were truly driven by pups' body mass relative to their current littermates rather than being a consequence of (epi)genetic effects potentially associated with their birth mass. In conclusion, our study underlines the importance of interactions among siblings in shaping individual differences in early growth and development largely independent of genetic factors. Highlights: In mammals, littermates are often a major part of the developmental environment. In rabbit pups, body temperature and growth depend on position in the litter huddle. Heavier littermates at birth occupy thermally more advantageous central positions. Does this advantage depend on genes or on relative differences in body mass? Cross-fostering showed that relative differences in body mass are decisive.